Risk Factors that Influence Hospital Length of Stay in Diabetic Foot Ulcer with Negative Pressure Wound Therapy at RS. dr. Cipto Mangunkusumo - Simbolon, Prabowo W; Ibrahim, Hilman (The New Ropanasuri Journal of Surgery, 2020)
Introduction. It is estimated that around 15% of diabetic patients will experience diabetic foot ulcer (DFU) in their lifetime. Negative Pressure Wound Therapy (NPWT) is proven to be more effective than conventional treatments. NPWT creates a moist wound environment, increases local blood flow and stimulates tissue granulation thereby accelerating wound healing. This study was conducted to determine the risk factors that affect the length of stay of DFU with NPWT. Knowing this risk factors may be helpful for optimizing management strategy. Method. This research was a retrospective study with a cross-sectional analytic design in 105 subjects treated in January 2016 to December 2018 at RS. dr. Cipto Mangunkusumo. Patient characteristics, demographics and risk factors were taken from medical records. The length of stay of the patient from the first application of NPWT to its outcomes was the main result, then the correlation to the risk factors that influence it was analyzed. Results. The length of stay of DFU with NPWT was 19.9 ± 19.3 days. Risk factors affecting the length of stay were history of ulcers (r = 0.01; p = 0.034), wound depth (r = 0.292; p = 0.003), Hb (r = 0.05; p = 0.039), HbA1c (r = 0.06; p = 0.033), Albumin (r = 0.06; p = 0.017), PCT (r = 0.10; p = 0.035), and duration of DM (r = 0.193; p = 0.009). Conclusion. This study showed that the length of stay of DFU with NPWT was influenced by systemic factors (duration of DM, Hb, HbA1c, albumin, and PCT) and local factors (history of previous ulcers and wound depth). The depth of the wound was the most positively related factor to the length of stay in DFU post NPWT (r = 0.292; p = 0.003). Interventions on factors that can be corrected before the application of NPWT may amplify the result of NPWT and reduce the length of treatment.